A conserved and regulated mechanism drives endosomal Rab transition - Lars Langemeyer; Ann-Christin Borchers; Eric Herrmann; Nadia Füllbrunn; Yaping Han; Angela Perz; Kathrin Auffarth; Daniel Kümmel; Christian Ungermann (eLife, 2020)
Endosomes and lysosomes harbor Rab5 and Rab7 on their surface as key proteins involved in their identity, biogenesis, and fusion. Rab activation requires a guanine nucleotide exchange factor (GEF), which is Mon1-Ccz1 for Rab7. During endosome maturation, Rab5 is replaced by Rab7, though the underlying mechanism remains poorly understood. Here, we identify the molecular determinants for Rab conversion in vivo and in vitro, and reconstitute Rab7 activation with yeast and metazoan proteins. We show (i) that Mon1-Ccz1 is an effector of Rab5, (ii) that membrane-bound Rab5 is the key factor to directly promote Mon1-Ccz1 dependent Rab7 activation and Rab7-dependent membrane fusion, and (iii) that this process is regulated in yeast by the casein kinase Yck3, which phosphorylates Mon1 and blocks Rab5 binding. Our study thus uncovers the minimal feed-forward machinery of the endosomal Rab cascade and a novel regulatory mechanism controlling this pathway.